2021
DOI: 10.1002/admt.202100124
|View full text |Cite
|
Sign up to set email alerts
|

Flow Analysis of Regenerated Silk Fibroin/Cellulose Nanofiber Suspensions via a Bioinspired Microfluidic Chip

Abstract: The outstanding performance of silk, especially in terms of mechanical properties, can be attributed to the sophisticated silk gland and specialized spinning method that exists in nature. In addition, the gland, with decreasing diameter, has been proven to be an outstanding actuator of the sophisticated spinning system. [5,9] It has been qualitatively demonstrated that a region of contracting geometry of the S-shaped duct of silk gland can induce stretching of protein molecules, phase separation, and self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…By using this natural spinneret, silk fiber with excellent comprehensive performance can be obtained at normal temperature and pressure. Biomimetic spinning by microfluidic chip refers to this structure and environment might obtain fiber materials with high performance and has become an important research topic in the construction of RSF fiber [ [58] , [59] , [60] ]. In addition, some conventional wet spinning and dry spinning methods have also been attempted to fabricate RSF fibers [ 61 , 62 ].…”
Section: From Building Blocks To Rsf Materials With Controllable Form...mentioning
confidence: 99%
“…By using this natural spinneret, silk fiber with excellent comprehensive performance can be obtained at normal temperature and pressure. Biomimetic spinning by microfluidic chip refers to this structure and environment might obtain fiber materials with high performance and has become an important research topic in the construction of RSF fiber [ [58] , [59] , [60] ]. In addition, some conventional wet spinning and dry spinning methods have also been attempted to fabricate RSF fibers [ 61 , 62 ].…”
Section: From Building Blocks To Rsf Materials With Controllable Form...mentioning
confidence: 99%
“…In addition to the aforementioned online investigations, it is worth mentioning the growing interest in coupling SAXS (or SANS) with suitable microfluidic devices for the in situ characterization of hard solid nanoparticles, including nanocrystals, silk fibers, and millimeter-sized supercrystals [ 41 , 42 , 43 , 55 , 56 , 57 , 86 ]. For instance, Chen et al reported through in situ UV–vis, and time-resolved microfocus SAXS experiments on the formation process of monodispersed gold nanoparticles with different sizes in a stopped-flow microfluidics ( Figure 5 A) [ 86 ].…”
Section: In Situ Structural Dynamics and Kinetic Formation Investigat...mentioning
confidence: 99%
“…Here, 2D and 3D microfluidic platforms are attractive for real-time tracking analysis of nucleation and monitoring of growth mechanisms of hard metal nanocrystals [ 39 , 40 , 41 , 42 , 43 ], in situ (online), high-throughput protein structure screening and analysis during crystallization processes and under various conditions [ 44 , 45 ], real-time monitoring of structural dynamic events during the generation of nano-self-assemblies [ 5 , 28 , 30 , 31 , 46 , 47 ], and online self-assembly behavior of amphiphiles or macromolecules under flow conditions [ 44 , 46 , 48 , 49 , 50 , 51 ]. Further, the use is extended to other research areas, including in situ characterization studies for monitoring the dynamic structural events during the digestion of drug formulations [ 52 ], the exposure of charged nano-self assemblies to divalent ions [ 53 , 54 ], the spinning process of artificial fibers [ 55 ], the generation of single domain supercrystals [ 56 ], the precipitation of crystals in moving droplets [ 57 ], and the nanoparticle agglomeration [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding sets the path for further research into the demystification of the enigma of the natural spinning process. It offers a complete and methodical look at the process of creating highly oriented artificial fibres for biological applications [118]. In the development, regeneration and characterization of a blended system combining Bombyx Mori silk fibroin protein and cellulose acetate, a cellulose derivative, silk may be mixed with cellulose derivatives [119].…”
Section: Design Of Cellulose With Microfluidicsmentioning
confidence: 99%
“…In the development, regeneration and characterization of a blended system combining Bombyx Mori silk fibroin protein and cellulose acetate, a cellulose derivative, silk may be mixed with cellulose derivatives [119]. Many studies on the combination of silk and cellulose acetate for filament/fibre manufacturing may be found in the literature [106,114,118,[120][121][122][123][124][125][126][127][128].…”
Section: Design Of Cellulose With Microfluidicsmentioning
confidence: 99%